Inhibition of glioma cell growth and tumorigenic potential by CCN3 (NOV). Issue 5 (1st October 2001) - Gupta, N; Wang, H; McLeod, T L; Naus, C C G; Kyurkchiev, S; Advani, S; Yu, J; Perbal, B; Weichselbaum, R R
Abstract : Aims —To establish whether the ectopic expression of CCN3 (NOV) in glioma cells can interfere with their tumorigenic potential and assess its potential value in molecular medicine. Methods —Glioma cell lines were used to assess whether differences in the degree of intracellular communication induced by the expression of the gap junction protein connexin 43 (Cx43) is related to the differential expression of CCN3 (NOV). The antiproliferative activity of rat CCN3 (rCCN3; NOV) in glioma cells, has been assessed both in vitro and in vivo with glioma cell lines expressing different amounts of CCN3 (NOV). Results —Upon ectopic expression of Cx43, the growth of C6 glioma cells is decreased. An increase of CCN3 (NOV) expression matches the reduced tumorigenic potential of these transfected cells. The localisation of CCN3 (NOV) is affected by the increased expression of Cx43 in the Cx-13 transfected cells, in which it is detected at areas of cell–cell contact. In a xenograft model, CCN3 (NOV) transfected glioma cells were found to induce tumours to a lesser degree than their parental counterparts, which do not express detectable amounts of CCN3 (NOV). Conclusions —Previous observations had suggested an inverse relation between CCN3 (NOV) expression in glioma cells and their tumorigenicity. These results establish a direct association between the establishment of functional gap junctional intercellular communication and the expression of rCCN3 (NOV). In addition to a negative effect on murine and human cell growth, CCN3 (NOV) has antiproliferative activity on tumour cells in vivo. Thus, the antiproliferative activity of the CCN3 (NOV) protein might involve reorganisation of cellular contacts that play a crucial role in tumorigenesis. The antiproliferative activity of CCN3 (NOV) established in this work sets the stage for the potential use of CCN proteins in molecular oncology.